2019
DOI: 10.1016/j.healthpol.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Earlier detection of public health risks – Health policy lessons for better compliance with the International Health Regulations (IHR 2005): Insights from low-, mid- and high-income countries

Abstract: a b s t r a c tThe International Health Regulations (IHR 2005) require all Member States to build and maintain the capacities to prevent, detect and respond to public health emergencies. Early detection of public health risks is one of the core functions. In order to improve surveillance and detection, a better understanding of the health system conditions and their influencing factors are needed. The Israeli Ministry of Health/IHR National Focal Point held a workshop to elucidate health system conditions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…The different types and sources of knowledge varied across studies, with many studies describing the exchange of multiple types of knowledge. The majority of studies (n = 70) described the exchange of research evidence and data [24,26,[31][32][33][34]36…”
Section: Ke Mechanisms and Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The different types and sources of knowledge varied across studies, with many studies describing the exchange of multiple types of knowledge. The majority of studies (n = 70) described the exchange of research evidence and data [24,26,[31][32][33][34]36…”
Section: Ke Mechanisms and Activitiesmentioning
confidence: 99%
“…Eight studies reported the use of active KE and concerned the response stage of a pandemic [31,32,35,43,48,53,55,61] involving mainly exchange between researchers and policy/practitioners [31,32,35,43,48]. Exchange involving lay knowledge was reported in three of these studies [53, 55,61].…”
Section: Pandemic Crisesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diese Methoden haben bei der Früherkennung von Infektionserkrankungen eine besondere Bedeutung, denn je früher diese erkannt werden, desto schneller kann die Weiterverbreitung gestoppt werden [ 34 , 35 ]. Die Internationalen Gesundheitsvorschriften (IHR 2005) tragen zur Entwicklung von Methoden bei, die es erlauben, Ausbrüche früher zu erkennen und dabei auf die Ortskenntnis und Aufmerksamkeit der Menschen vor Ort zu setzen [ 36 ]. Mithilfe der Soziallabormethode konnten bei der Bekämpfung des Ebolaausbruchs 2014/2015 in Westafrika tatsächlich neue Wege zum Infektionsmanagement gefunden werden [ 37 ].…”
Section: Neue Herangehensweisen An Die Risikokommunikation In Public-...unclassified
“…Die Gesundheitsämter müssen diese Informationen aufnehmen, bewerten und mit regionalen Kollegen teilen und gleichzeitig erkennen, dass es ein Ausbruch ist, und angemessene Interventionen zur Eindämmung einleiten. Dieses Konzept zur Früherkennung von Krankheitsausbrüchen wird aktuell für Public-Health-Notlagen aufgearbeitet [ 34 , 36 ].…”
Section: Neue Herangehensweisen An Die Risikokommunikation In Public-...unclassified